The Influence of Social and Environmental Factors on the Behavior of Using Personal Protective Equipment (PPE) When Driving on Students of SMK Muammadiyah Aek Kanopan in North Labuhan Batu Regency: Cross Sectional Study - Fauziah Gusvita Syarah; Nayodi Permayasa; Asdi Lastari; Dwiana Kartika Putri (International Journal of Health Engineering and Technology, 2025)
Traffic safety is one of the important aspects in community life that is often ignored, especially by the adolescent age group. Students are a productive age group who often use motorbikes as their main means of transportation to school or other activities. This makes them one of the groups that are vulnerable to traffic accidents, especially when they do not use Personal Protective Equipment (PPE) when driving. To analyze the Influence of Social and Environmental Factors on the Behavior of Using PPE for Driving on Students of SMK Muammadiyah Aek Kanopan in North Labuhanbatu Regency, the type of observational study with a cross-sectional design, the population of all students in grades X and XI, as many as 330 people. From the population, a sample of 142 respondents was determined in 2025, the sampling technique used a non-probability sampling technique with a purposive sampling method, Peer Influence = p (0.001), Traffic Safety Education Received at School = p (0.001), Distance from Home to School = p (0.001), Access to Proper PPE = p (0.001) have an effect on the use of PPE while driving. While the most influential variable is traffic safety education received at school (Exp (b) = 7.984. This study concludes that peers, traffic safety education, distance from home to school, and access to PPE have a significant effect on the use of PPE while driving, with traffic safety education as the most dominant factor.